Kaedah Pendidikan Akuntansi dalam Konsep Ekonomi Syariah - Hidayat, Taufik (Sekolah Tinggi Agama Islam Negeri Curup, 2016)
The development of world indicated an acceleration of human lifes. It makes human act to be legatimated trought law, norm and ethics. It also strive for islamic role to be legalized of human actionâbussiness, and others. It is a signifier of shariah principles implementation. In this context, shariah accounting is a main pillars of implemented-shariah principles in accounting processs. Theoritically, shariah accounting is socio-economics disciplines of which was formulated from shariah values, and norms. Its goal is to control the human actâbussiness, and also avoid them from savage mind, corrupt behavior. The paper applies the library study in order to clearly formulate various concept of islamic accounting in Islam. Keywords : Education, Shariah Accounting, Kaffah, Islamic Economics, and Socio-Economics.